Feasibility of Variety Chicken Businessesthe Domestic Fallandpama-Khoy In The Villagemiddle Consciousness - Sri Purwanti; Dimas Ganda PermanaSon; Yuni Rositagoddess; ZainulArifin (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
Cultivating gallus domestic and pama-khoy chicken varieties in Sadartengah Village is very profitable because the selling price is quite high for both gallus domesticus and pama-khoy chickens. Gallus domesticus and pama-khoy chicken varieties can be sold at the age of 6 months. The need for care for these varieties of chickens is easy to get at quite affordable prices. This study uses a combination of methods, namely qualitative and quantitative. Data collection was carried out by interview, observation and documentation techniques. Based on the research results, it was found that a good way to cultivate chickens of the Gallus domesticus and pama-khoy varieties is by paying attention to and meeting the needs of the chickens in terms of food given according to meal times, a chicken coop as a place for shelter and a place for the chickens to live and preventing predators, providing vitamins, as well as electricity for lamps to provide lighting in the chicken coop. The income from the Gallus domesticus chicken business is IDR. 1,556,200, which is less than the income of pama-khoy chicken, which is Rp. 3,936,200. Comparison of the suitability of the Gallus domesticus and Pama-khoy chicken varieties with the R/C ratio of production for Gallus domesticus chickens is 1.69, smaller than Pama-khoy chickens, namely 2.77.